Political Theology through a History of Preaching: A Study in the Authority of Celebrity (Homiletic, 2017)
This article shows some of the ways that historical studies of preaching can open into normative reflections on political life. A focus on embodied practices reveals the ways those practices circulate between religious, political, and other spheres of society. This transmigration of practice means that reform in one sphere leads to changes in others. Practical theology becomes public theology. And the ritual and rhetorical forms of preaching can have at least as much political significance as any overtly political content of sermons. The argument proceeds through an extended case study of the ways that Charles G. Finney’s techniques for preaching helped create a distinctive authority of celebrity that has grown in significance for late modern mass democracies.